Airborne laser scanning (ALS) point clouds with full-waveform (FWF) data of central European forest plots, Germany [dataset] - Weiser, Hannah; Winiwarter, Lukas; Schäfer, Jannika; Faßnacht, Fabian Ewald; Höfle, Bernhard (PANGAEA - Data Publisher for Earth & Environmental Science, 2022)
Full-waveform (FWF) airborne laser scanning (ALS) data were acquired in southwest Germany in July 2019. We clipped the data to the extent of the 12 forest plots described in the related data publication (https://doi.org/10.1594/PANGAEA.942856), which means that they overlap with the UAV-borne and terrestrial laser scanning data presented in that publication. The plots are located in mixed central European forests close to Bretten and Karlsruhe, in the federal state of Baden-Württemberg, Germany.